Reevaluating Moral Education: Addressing Bullying in Schools Through a Collaborative Framework - Darwin; Muhammad AR; Silahuddin (Indonesian Values and Character Education Journal, 2024)
Bullying in educational settings remains a significant challenge, despite the integration of moral education into the curriculum aimed at shaping students' character and reducing negative behaviors. This study aims to explore the effectiveness of moral education in addressing bullying while identifying barriers to its success. The research employed a mixed-methods approach, combining quantitative surveys and qualitative interviews with students and educators as participants. Data were analyzed thematically and through descriptive statistics to provide a comprehensive understanding. The key findings reveal a discrepancy between the moral values taught in schools and students' daily behavior. Barriers include inconsistent application of moral values, external influences such as social media, limited family involvement, and an overemphasis on formal religious practices without the internalization of moral values. This study concludes that a systematic and collaborative approach involving schools, families, and communities is essential to effectively reduce bullying, including refining moral education with a more comprehensive and practical approach applicable to students’ daily lives.